KONSEP WILAYAH AL-HISBAH DALAM ISLAM DAN APLIKASINYA DALAM SISTEM PENGAWASAN PASAR DI KABUPATEN TANAH DATAR - Fadli Fadli (IAIN Batusangkar, 2015)
This research focused on Islamic concept of Wilâyah al-Hisbah and its implementation toward the monitoring market system in Tanah Datar. This research belongs to descriptive qualitative by applying interview and documentation as instruments. The results revealed that the concept of Wilâyah al-Hisbah followed the theory Abu Yusuf, Imam al-Ghazali and Ibn Taymiyah. The government of Tanah Datar also participated in economic activities include monitoring the market in Tanah Datar. The monitoring was related to price monitoring; commodities traded both in terms of quantity and material contained; oversight of the accuracy on the scales; the arrangement of the market; demolition and other market participants. Nevertheless, there were still weaknesses in the monitoring market, such as the persistence of circulating goods that harm the public like contains alcohol, home industry uses hazardous substances that could endanger public health. Keywords: Islamic Concept and Implementation of Wilâyah al-Hisbah, Monitoring Market System,Tanah Datar.